Molecular detection and assemblage analysis of the intestinal protozoan Giardia duodenalis in wild boars in Korea - Lee, Haeseung; Kwak, Dongmi (Frontiers in Veterinary Science, 2023)
Giardia duodenalis (syn. G. intestinalis, G. lamblia) is the only Giardia species that infects humans, as well as most other mammals. Wild boars are a reservoir of many viruses, bacteria, and parasites that can be transmitted to livestock and humans. This study examined the infection rate of G. duodenalis in wild boars and confirmed its specificity by comparing genotypes through PCR amplification of the 18S rRNA, gdh, and β-giardin genes. Fecal samples were collected from roadkilled or trapped wild boars throughout Korea from April 2016 to December 2021. DNA was extracted directly from a total of 612 wild boar fecal specimens using a commercial kit. PCR was carried out targeting the 18S rRNA region, β-giardin, and glutamate dehydrogenase genes of G. duodenalis. Some PCR-positive samples were selected for sequencing analysis, and the obtained sequences were subsequently used for phylogenetic tree construction. Of the 612 samples tested, 125 (20.4%) were positive for G. duodenalis. According to the studied regions and seasons, the highest infection rate was detected in the central region (12.0%) and in the autumn (12.7%). Phylogenetic analysis identified three genetic assemblages A, B, and E. Assemblages A and B presented a 100% identity with Giardia sequences isolated from human and farmed pigs in Korea and Japan. This result, which indicates the possibility of zoonotic transmission, cannot be ignored, and continuous management and monitoring of this pathogen are necessary to prevent transmission and protect both animal and human health.